1993
DOI: 10.1002/bjs.1800800339
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer and Helicobacter pylori infection

Abstract: Gastric adenocarcinoma can be divided into two histopathological types: intestinal and diffuse. In addition to the role of environmental factors, an association between gastric cancer and Helicobacter pylori has been suggested. A retrospective study was therefore carried out among 46 patients who had gastric cancer. As a control group, 40 patients with non-malignant disorders were selected (11 patients with peptic ulcer, 12 with chronic superficial gastritis, 17 with chronic atrophic gastritis). Twenty-six can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 20 publications
2
6
0
3
Order By: Relevance
“…Reports concerning the association of H pylori with histological types of gastric cancers are controversial. Some studies have shown an association between H pylori and intestinal type [2,30] , while others have observed a balanced distribution between the two histological types, like in the present work [31,32] . Some works have shown an association between Bcl-2 expression and EBV-positive gastric carcinomas [9] .…”
Section: Discussionsupporting
confidence: 61%
“…Reports concerning the association of H pylori with histological types of gastric cancers are controversial. Some studies have shown an association between H pylori and intestinal type [2,30] , while others have observed a balanced distribution between the two histological types, like in the present work [31,32] . Some works have shown an association between Bcl-2 expression and EBV-positive gastric carcinomas [9] .…”
Section: Discussionsupporting
confidence: 61%
“…After H. pylori infection becomes established, the gastric epithelium and the glands in the lamina propria are damaged both by direct bacterial toxicity and by the effects of inflammatory cell infiltration. Thus, chronic H. pylori infection may contribute to the process of mucosal destruction and regeneration in atrophic gastritis, with such changes being closely related to the occurrence of gastric cancer [3,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Tradicionalmente, la localización más frecuente del cáncer gástrico es la región antropilórica (cáncer gástrico distal) (5,6) , el cual se relaciona con el tipo histológico intestinal. Sin embargo, en las últimas décadas se ha observado un incremento de la frecuencia de los tumores de cuerpo y fondo (cáncer gástrico proximal) y de la unión esófago-gástrica (7)(8)(9) , lo cual se sospecha está asociado al cambio en la prevalencia también del tipo histológico de cáncer gástrico hacia el tipo difuso (10,11) .…”
Section: Introductionunclassified